Pengaruh Pelatihan Kewirausahaan dan Akses Permodalan Terhadap Perkembangan Usaha Jasa Mini ATM Di Kec. Medan Johor - Arief, Sulthan Ananda; Putra, Irwansyah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine “The Effect of Entrepreneurship Training and Access to Capital on the Development of Mini ATM Services in Medan Johor District.” The research method used is quantitative with a causal associative approach. The population in this study consists of 119 Mini ATM service business operators located in Medan Johor District, and the sample consists of 54 business operators, which were selected using purposive sampling. The research data is sourced from primary data, where questionnaires were distributed directly to respondents to obtain research data. Based on the partial test results, it was concluded that entrepreneurship training and access to capital had a positive and significant effect on the development of Mini ATM services, access to capital had a positive and significant effect on the development of Mini ATM services, and the simultaneous results concluded that entrepreneurship training and access to capital had a positive and significant effect on the development of Mini ATM services in Medan Johor District. In addition, the coefficient of determination (R²) test found an Adjusted R Square value of 0,263. This value indicates that the variables of entrepreneurship training (X1) and access to capital (X2) are able to explain 26,3% of the variation in business development (Y), while the remaining 73,7% is influenced by other factors not analyzed in this study.